2005
DOI: 10.1111/j.1467-789x.2005.00184.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity prevention: a proposed framework for translating evidence into action

Abstract: Obesity as a major public health and economic problem has risen to the top of policy and programme agendas in many countries, with prevention of childhood obesity providing a particularly compelling mandate for action. There is widespread agreement that action is needed urgently, that it should be comprehensive and sustained, and that it should be evidence-based. While policy and programme funding decisions are inevitably subject to a variety of historical, social, and political influences, a framework for def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
309
0
12

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 351 publications
(324 citation statements)
references
References 33 publications
3
309
0
12
Order By: Relevance
“…Moreover, participants highlighted varying learning styles, scheduling accommodations, computer access limitations, and didactic preferences that suggested the modification of choice of course delivery mode (online or FTF) rather than random assignment to intervention modality as originally planned. This modification to our study design improved our ability to reach students at the schools and enhanced our chances of implementing the intervention successfully, both of which are key components of community obesity prevention approaches [22,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, participants highlighted varying learning styles, scheduling accommodations, computer access limitations, and didactic preferences that suggested the modification of choice of course delivery mode (online or FTF) rather than random assignment to intervention modality as originally planned. This modification to our study design improved our ability to reach students at the schools and enhanced our chances of implementing the intervention successfully, both of which are key components of community obesity prevention approaches [22,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…proposed by Swinburn et al (1) is sufficient to combat the obesity epidemic. Recent studies from our group have shown that weight gain is due to a relatively small positive energy balance (43) .…”
Section: Limitationsmentioning
confidence: 97%
“…There is a consensus that public health actions for overweight prevention and control should adopt ecological models that recognise the existence of multiple factors associated with weight gain (8,9) .…”
mentioning
confidence: 99%